THE EVALUATION OF ENHANCING CHARACTER EDUCATION PROGRAM: Empirical Study using the Context, Input, Process, and Product (CIPP) Method at Buddhist Colleges in Banten - Suparmanto; Prof. Dr. Billy Tunas; Dr. Widodo Sunaryo (SUJANA: Education and Learning Review, 2023)
This research aims to find efforts and strategies to improve the character education strengthening program by producing recommendations for the continuation of the next character education strengthening program. This research uses the Context, Input, Process, and Product (CIPP) method with the samples in this research are Lecturers, Rector/Director of Higher Education and Higher Education Officials of the Ministry of Education and Culture related to the Character Education Strengthening Program at Buddhist Universities in Banten. The results of character education strengthening program at the Buddhist Colleges in Banten takes the form of outputs and outcomes in order to form graduates of Buddhist Colleges with national character. Based on the results of the CIPP analysis, in the Context component, the character education strengthening program at Buddhist Colleges in Banten includes aspects of requirements analysis, the objectives, targets and policies getting "Good" evaluation results, in the Input component which includes aspects of resources, organization and infrastructure after going through the evaluation getting a range of "Good", the Process component of the character education strengthening program at Buddhist Colleges in Banten includes work procedures, activity schedules and implementation processes, based on the results of the evaluation getting "Adequate", the Product component which includes Output and Outcomes based on the results of the evaluation getting "Adequate." The assessment of the effectiveness of the character education strengthening program in the scope of education in general, is quite effective because this character education strengthening program refers to the priority of certain values that will be the focus of learning, understanding, understanding, and practice in order for character education to change the behavior, way of thinking, and way of acting of the entire Indonesian nation to be better and have integrity.